Analysing dairy business value chains in far-western terai districts of Nepal - Bhandari, T. (Journal of the Institute of Agriculture and Animal Science, 2018)
Dairy sub-sector is recognized as fast growing profitable agro-business in far-western Terai districts but past studies to support that statement is lacking. The field survey was conducted from February to April 2012 with the aim to analyse business capabilities of operational service providers, investigating value chain analysis and market analysis of the overall milk business. The study collected primary information from 103 respondents by applying multi-stakeholder discussions along with constraint-opportunity analysis. The identified value chain functions were: input supply, milk production, collection, chilling, processing, trading and consumption. The major business stakeholders included 28 private dairies, 34 milk producing cooperatives,7 chilling centres, Dhangadhi Milk Supply Scheme, 25 milk vendors, 44 sweet houses, and more than 100 hotels and restaurants which were transacting 20800 tons equals milk and milk products. Value margin analysis revealed that milk producers were earning higher profit in comparison to the additional cost required for product transformation. Nevertheless, accounting dominance of services offered ultimately on market functions, private dairies were capturing higher profit margins through retailing short shelf-life products disposing through local market outlets. Gross margin analysis on few dairy products sold by the private dairies revealed that selling curd, paneer, Khoa, and ice cream were respectively two times, five times and twenty times profitable, than the selling standard milk. The market analysis indicated 26 percent higher supply of milk in flush season months to the end market outlets. The leverage point of future interventions were: immediate need of preparing at and working upon dairy business plan in coordination across value chains actors, strengthening backward linkage particularly input and production management, and encouraging to manufacture long shelf-life dairy products. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, page: 269-281